Jakarta Islamic Index (JII) in The Context of Investigating Financial Ratios as Determinant of Company Share Returns - Khoirul Umam Hasbiy; Abdul Basir; Nurmawati Mambuhu; Alfiana Alfiana; Fredy Olimsar (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to analyze the effect of ROA, EPS on stock returns in companies listed on the Jakarta Islamic Index (JII). The population in this study are companies listed on the Jakarta Islamic Index (JII) during the 2018-2022 period. Sampling was done by purposive sampling method with a sample of 20 companies. The type of data used is secondary data obtained through the company's financial statements and annual reports which can be accessed through the official website of the Indonesia Stock Exchange (www.idx.co.id) or the official website of the company. The data analysis technique used is multiple linear regression. The results of this study indicate that the ROA variable affects stock returns in companies listed on the Jakarta Islamic Index (JII) while the EPS variable has no effect on stock returns in companies listed on the Jakarta Islamic Index (JII).